Pengembangan Komik Berbasis Pendekatan Komunikatif pada Pembelajaran Bahasa Indonesia Untuk Siswa Kelas III di Sekolah Dasar - Laura Renita; M. Dafa Ananda (Universitas Palan, 2024)
This research aims to develop comics based on a communicative approach. This research is included in the research and development (R&D) model. This research uses the ADDIE model. The ADDIE model is an abbreviation for Analyze, Design, Develop, Implement, and Evaluate. This research has only reached the development stage. The research was conducted at SD Negeri 053977 Gohor Lama. The subjects in the research were 18 class III students, consisting of 12 female students and 6 male students. The object of research is comics based on a communicative approach. Data collection techniques are observation, interviews and tests. Based on the research results, it is known that the validation results carried out by material experts were 93.78% with very feasible criteria. Meanwhile, the media expert's results were 90.20% with very feasible criteria. Based on the validation results, it can be concluded that comics based on a communicative approach are very suitable for use by class III students at SD Negeri 053977 Gohor Lama.